PENGARUH THIN CAPITALIZATION, RELATED PARTY TRANSACTION, DAN PROFITABILITAS TERHADAP TAX AVOIDANCE (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2022) - Sofha, Nurhaliza Maridha; Rohman, Abdul (Diponegoro Journal of Accounting, 2024)
The research aims to test hypotheses and produce empirical findings related to the effect of thin capitalization, related party transactions, and profitability on tax avoidance. This study used purposive sampling techniques. The data used in this study are the financial statements of manufacturing companies listed on the IDX during the period 2019 – 2022 with a sample of 106. Hypothesis testing in this study used multiple linear regression analysis with the help of SPSS program version 26.The independent variables used are thin capitalization, related party transactions, and profitability. The measurement used to measure thin capitalization is proxied by debt to equity ratio and related party transaction is proxied using related party transaction liabilities, while profitability is measured by return on assets. In addition, the dependent variable in the form of tax avoidance is proxied using an effective tax rate.The results showed that thin capitalization had no effect on tax avoidance. Related party transactions have a positive and significant effect on tax avoidance, while profitability has a negative and significant effect on tax avoidance.